2005
DOI: 10.1016/j.joca.2005.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Altered cartilage mechanics and histology in knee osteoarthritis: relation to clinical assessment (ICRS Grade)

Abstract: The results indicate a relation between structural, mechanical and histological changes in all stages of the degeneration. With increasing ICRS Grade the cartilage stiffness, which is primarily influenced by the integrity of the extracellular matrix, decreases. Therefore, methods of stiffness determination such as indentation may be used to characterize cartilage in all stages of OA. However, the data suggest that differentiating between healthy cartilage and ICRS Grade 1 may be difficult using mechanical test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
176
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(195 citation statements)
references
References 34 publications
13
176
0
6
Order By: Relevance
“…Once triggered, degeneration is marked by a vicious circle of increasing structural changes that are not homogenous across the joint, but usually extend out from a localized area. 8 In line with this theory, Kleemann et al found substantial statistical variation in histological Mankin scores in relation to the Outerbridge grade, 19 which supports the present study's findings of a close relation between degeneration and variation.…”
Section: Discussionsupporting
confidence: 90%
“…Once triggered, degeneration is marked by a vicious circle of increasing structural changes that are not homogenous across the joint, but usually extend out from a localized area. 8 In line with this theory, Kleemann et al found substantial statistical variation in histological Mankin scores in relation to the Outerbridge grade, 19 which supports the present study's findings of a close relation between degeneration and variation.…”
Section: Discussionsupporting
confidence: 90%
“…However, in this case, the concentration of the external bath solution was decreased from 0.15 to 0.125 M to mimic cartilage swelling observed in the physiological situation. Both computational parameters for OA progression and cartilage after full joint immobilization were obtained from the literature [49][50][51][52][53]. The related results were compared with those obtained for healthy tissue.…”
Section: Numerical Applicationsmentioning
confidence: 99%
“…The severity of cartilage injury was classified into the following 5 grades according to the International Cartilage Repair Society (ICRS) classification 10) : Grade 0, normal; Grade 1, softening and fissure of cartilage; Grade 2, cartilage defect of less than 50%; Grade 3, cartilage defect of more than 50% ; and Grade 4, defect extending to the subcartilaginous bone. In this study, severe cartilage injury was classified as Grade 3 or 4, and the number of such injuries was calculated.…”
Section: Distribution and Severity Of Cartilage Injury In The Radial mentioning
confidence: 99%
“…The severity of cartilage injury was classified according to the ICRS system, 10) as was the radial notch of the ulna. Similarly, severe cartilage injury was classified as Grade 3 or 4, and the number of such injuries was calculated.…”
Section: Distribution and Severity Of Cartilage Injury In The Articulmentioning
confidence: 99%